Social functioning in children with brain insult - Greenham, Mardee; Spencer-Smith, Megan M.; Anderson, Peter J.; Coleman, Lee; Anderson, Vicki A. (Frontiers in Human Neuroscience, 2010)
Social dysfunction is commonly reported by survivors of brain insult, and is often rated as the most debilitating of all sequelae, impacting on many areas of daily life, as well as overall quality of life. Within the early brain insult (EBI) literature, physical and cognitive domains have been of primary interest and social skills have received scant attention. As a result it remains unclear how common these problems are, and whether factors predictive of recovery (insult severity, lesion location, age at insult, environment) in other functional domains (motor, speech, cognition) also contribute to social outcome. This study compared social outcomes for children sustaining EBI at different times from gestation to late childhood to determine whether EBI was associated with an increased risk of problems. Children with focal brain insults were categorized according to timing of brain insult: (i) Congenital (n = 38): EBI: first–second trimester; (ii) Perinatal (n = 33); EBI: third trimester to 1 month post-natal; (iii) Infancy (n=23): EBI: 2 months–2 years post-birth; (iv) Preschool (n = 19): EBI: 3–6 years; (v) Middle Childhood (n = 31): EBI: 7–9 years; and (vi) Late Childhood (n = 19): EBI: after age 10. Children’s teachers completed questionnaires measuring social function (Strengths and Difficulties Questionnaire, Walker McConnell Scale of Social Competence and School Adjustment). Results showed that children with EBI were at increased risk for social impairment compared to normative expectations. EBI before age 2 years was associated with most significant social impairment, while children with EBI in the preschool years and in late childhood recorded scores closer to normal. Lesion location and laterality were not predictive of social outcome, and nor was social risk. In contrast, presence of disability (seizures) and family function were shown to contribute to aspects of social function.